Análisis jurídico social del delito de robo simple en la legislación ecuatoriana, cantón Latacunga, provincia de Cotopaxi. - Romero Ibáñez, Freddy Washington (2013)
In recent years, several proposals from different sectors of society have been performed in order to propose anew penal legislation, according to different concepts, policies and visions of crime that currently to strike at Ecuadorian society, they do not give the expected results, because from my perspective there is no clear policy to directly combat the commission of crimes, especially simple robbery. In some cases, certain patches policies have been implemented, which not evident solutions for the short, medium and long term is for this reason that this thesis makes a detailed analysis of the crimes of robbery simple, especially when you have the encouragement of ownership, because in recent times there have been various discussions, trying to find the best opinion, among which hold that it is simply a subjective element, it concludes by stating that the mood of appropriation is a subjective element of theft, as is also the wanting subtract, and converting that premise conclusion other reasoning, which leads to another important consequence: “Our substantive criminal law establishes essentially that simple thefts a crime that affects directly to equity and people". Another trial transcendental doctrine formulated several authors penalty is consider in gun fair some articles of the Criminal Code, which tend to determine the sentence abased on the value of the thing stolen, stating that "we think the value of things must be taken into consideration, not for these tensing, but exclusively for payment of compensation for damages".